Agenda for CART Breakfast with Dick Cheney, [CART Letter to Senators] (Tufts Archival Research Center, 2007)
Coalition Against Regressive Taxation (CART) agenda of meeting with Rep. Dick Cheney and letter to Senate members. Supports tax overhaul soon to be voted on by the Senate because of its aid to the lower class and because it contains no excise taxes. Urges Senate not to introduce excise taxes in the future.